2018
DOI: 10.1101/429746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrin alpha11 is an Osteolectin receptor and is required for the maintenance of adult skeletal bone mass

Abstract: We previously discovered a new osteogenic growth factor that is required to maintain adult skeletal bone mass, Osteolectin/Clec11a. Osteolectin acts on Leptin Receptor + (LepR + ) skeletal stem cells and other osteogenic progenitors in bone marrow to promote their differentiation into osteoblasts. Here we identity a receptor for Osteolectin, a11 integrin, which is expressed by LepR + cells and osteoblasts. a11b1 integrin binds Osteolectin with nanomolar affinity and is required for the osteogenic response to O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…57 ITGA11 has only recently been identified as a receptor of osteolectin, an osteogenic growth factor that also has been discovered recently, and is required for maintenance of adult skeleton and osteogenic potential of BMSCs. 58,59 It has been shown that ITGA11 signalling activates the canonical Wnt pathway, and blockage of the latter also annihilates the osteogenic effect of osteolectin. 58 While up-regulation of multiple integrins has been found in transcriptome analysis of human ASCs upon osteogenic differentiation, ITGA11 was not up-regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 ITGA11 has only recently been identified as a receptor of osteolectin, an osteogenic growth factor that also has been discovered recently, and is required for maintenance of adult skeleton and osteogenic potential of BMSCs. 58,59 It has been shown that ITGA11 signalling activates the canonical Wnt pathway, and blockage of the latter also annihilates the osteogenic effect of osteolectin. 58 While up-regulation of multiple integrins has been found in transcriptome analysis of human ASCs upon osteogenic differentiation, ITGA11 was not up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 It has been shown that ITGA11 signalling activates the canonical Wnt pathway, and blockage of the latter also annihilates the osteogenic effect of osteolectin. 58 While up-regulation of multiple integrins has been found in transcriptome analysis of human ASCs upon osteogenic differentiation, ITGA11 was not up-regulated. 43 How altering ITGA11-expression in ASCs affects their osteogenic potential is part of an ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that genes related to cell adhesion such as ITGA11 and insulin-like growth factor binding protein 7 (IGFBP7) also upregulated on day 25. Integrin α11 (ITGA11) is a receptor for osteolectin that actives the Wnt pathway and promotes osteogenesis [59]. Recently, Zhang et al also reported that the IGFBP7 gene promoted osteogenic differentiation of hBM-MSCs by upregulation of the βcatenin pathway [60].…”
Section: Genes In Focal Adhesion Signaling Promote Osteogenic Differementioning
confidence: 99%
“…Activation of Wnt/β-catenin and PI3K-Akt signaling pathways drive osteogenic differentiation upon primed α5β1 integrin using peptides in mesenchymal skeletal cells [85]. Another study showed that osteolectin/α11β1 results in Wnt pathway activation that increased nuclear β-catenin and finally promoted osteogenesis [59]. CDH11 is involved in osteoblast committed into the osteogenic lineage.…”
Section: Relationship Between Hub Genes and Wnt Pathway During Osteogmentioning
confidence: 99%
“…Triple-helical peptides (THPs) containing these motifs have been synthesised and are used throughout this study ( Emsley et al, 2000 ; Farndale, 2019 ; Knight et al, 2000 ; Zhang et al, 2003 ). Integrins α1β1 and α2β1 are widely expressed, whereas α10β1 is expressed primarily in chondrocytes ( Barczyk et al, 2010 ; Takada et al, 2007 ) and α11β1 is expressed in fibroblasts, subsets of mesenchymal stem cells and subsets of cancer-associated fibroblasts ( Zeltz and Gullberg, 2016 ; Popova et al, 2007 ; Popov et al, 2011 ; Shen et al, 2019 ; Zeltz et al, 2019 ; Zeltz et al, 2020 ). The range of pathways involving integrins highlights their importance in tissue function and homeostasis across a variety of organs.…”
Section: Introductionmentioning
confidence: 99%